2005
DOI: 10.1097/01.jnr.0000387536.60760.4e
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Quality of Sleep and Its Related Factors Among Menopausal Women

Abstract: Sleep, a basic physiological need of all humans, appears to be both integrative and restorative. However, studies have reported that 33-51% of women show a dramatic increase in sleep disturbance in the mid-life years, a time when they enter menopause. The purposes of this study were to (1) explore the prevalence of poor sleep quality in menopausal women; (2) identify the relationship between sleep quality of menopausal women and its related factors; (3) predict the possible explanations of how the related vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 9 publications
(37 reference statements)
3
26
1
1
Order By: Relevance
“…Moreover, the results indicated a significant difference between sleep quality and chronic disease status of the elderly, so that with an increase in chronic diseases in the elderly, their sleep quality was worsened, which was in line with the findings of Hsiu (Hsiu & Lin, 2005), Niu et al (Niu et al, 2016) and Wu et al (Wu, Tung-Ping Su, ChinLung Fang, & Mei Yeh Chang, 2012). Further, Park et al stated that chronic disease in the elderly was a predictor of their sleep quality (Park, Yoo, & Bae, 2013).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Moreover, the results indicated a significant difference between sleep quality and chronic disease status of the elderly, so that with an increase in chronic diseases in the elderly, their sleep quality was worsened, which was in line with the findings of Hsiu (Hsiu & Lin, 2005), Niu et al (Niu et al, 2016) and Wu et al (Wu, Tung-Ping Su, ChinLung Fang, & Mei Yeh Chang, 2012). Further, Park et al stated that chronic disease in the elderly was a predictor of their sleep quality (Park, Yoo, & Bae, 2013).…”
Section: Discussionsupporting
confidence: 79%
“…Additionally, the findings revealed no significant difference between sleep quality and duration of menopause among the female elderly. However, Hsiu et al (Hsiu & Lin, 2005) reported menopause played a key role in structural changes of elderly women's sleep, and they suffered sleep disorder after menopause.…”
Section: Discussionmentioning
confidence: 99%
“…This culturally dependent relationship between sleep disturbance and vasomotor symptoms might be explained by a much lower rate of vasomotor symptoms in Asian women (20%) than their Western counterparts (60%; Freeman & Sherif, 2007). Asian women's sleep quality tends to be more closely associated with psychological status such as anxiety or depression (Cheng et al, 2008;Chung & Tang, 2006;Hsu & Lin, 2005;Shin et al, 2005), age (Hsu & Lin, 2005;Shin et al, 2005), financial situation (Shin et al, 2005), and weight status (Cheng et al, 2008).…”
Section: Please Scroll Down For Articlementioning
confidence: 93%
“…Several studies were conducted on the quality of sleep in different countries (13)(14)(15)(16) and among older people (17).…”
Section: Introductionmentioning
confidence: 99%